Dichotic listening deficits in children with hearing loss. (May 2023) - Moncrieff, Deborah; Auld, Ruth; Johnston, Deborrah; Wirt, Tessa
Abstract: Purpose: This correlational study compared dichotic listening among children with significant hearing loss to typically developing children and children clinically assessed for auditory processing disorder. Method: Recorded versions of two dichotic tests were delivered under earphones or in the sound field for children using amplification. Individual ear scores and interaural asymmetry were compared to normative data. Matched deficit patterns from both tests were identified, ranked for severity of deficit, and compared across groups. Relationships between dichotic scores and factors related to amplification were investigated in the children with hearing loss. Results: Dichotic scores were significantly poorer among children with hearing loss without the large interaural asymmetries seen in children assessed clinically for auditory processing problems. Device type and age of implantation had no effect on scores; non-dominant ear scores on the digits test were significantly correlated to age of device use in the left ear and duration of device use in the right ear. Non-dominant ear scores with digits were also significantly correlated with bilateral word recognition. Conclusions: Poor dichotic perception in children with significant hearing losses may be related to the use of recorded test materials, immature skills in attention and working memory, or other factors that contribute to development of vocabulary and language. These weaknesses may interfere with successful mainstream educational placement in these children. Assessment of dichotic performance in this population could lead to deficit-specific interventions that may improve outcomes and enhance educational opportunities for children with hearing loss.